Pengaruh Daya Tarik Wisata, Aksesbilitas, Harga Dan Fasilitas Terhadap Minat Berkunjung Wisatawan Di Objek Wisata Pantai Bowele Kabupaten Malang - Harganes, Genta Dera; Khalikussabir, Khalikussabir; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the influence of tourist attractions, accessibility, price, and facilities on the decision to visit the Bowele beach tourist attraction in Malang Regency. The research method used is quantitative with an explanatory research approach. Data was collected through surveys using valid and reliable research instruments. Data analysis was carried out using statistical techniques to test the hypothesis proposed.The results of this study show that Tourist Attraction, Accessibility, Price, and Facilities simultaneously affect the Interest of Tourists Visiting Bowele Beach. And it partially shows that Tourist Attraction and Price have a significant positive effect, while Accessibility and Facilities do not have a significant negative effect. Keywords: Tourist Attractions, Accessibility, Prices, Facilities, Interest in Visiting